Effectiveness of gold sea cucumber (Stichopus hermanii) extracts in accelerating the healing process of oral traumatic ulcer in rats - Damaiyanti, Dian Widya; Soesilowati, Pratiwi; Arundina, Ira; Sari, Rima Parwati (Universitas Padjadjaran, 2019)
Introduction: Gold sea cucumber (Stichopus hermanii) is a marine organism that contains omega-3 and glycosaminoglycan for enhancing collagen needed in the healing process. This study was aimed to determine the effectiveness of gold sea cucumber extracts in accelerating the healing process of oral traumatic ulcer in Wistar rats, in terms of the correlation between collagen type I expression, ulcer diameter, and body weight loss. Methods: Twenty Wistar rats (Rattus norvegicus) was divided into four groups and treated with gold sea cucumber extracts with the concentration of 80%, 40%, and 20% in the form of 0.1 ml gel daily. The negative control group received no treatment. Ulceration of the lower lip of labial mucosa was induced by a burnisher. The animals were observed for 7 days, during which they were weighed and the ulcers diameter was measured. The rats were then sacrificed after 7 days of treatment. Histometric analysis of collagen type I expression was also performed. Data obtained were analysed for differences between the group with one-way ANOVA test and the correlation was analysed with the Pearson test. Results: The significant differences (p < 0.05) between treatment groups was found in the ulcer diameters and the collagen type I expression. The most decreased ulcer diameter and the highest collagen type I expression detected in the group of treatment with a concentration of 80% — no significant differences found in the weight loss between-groups (p > 0.05). Strong correlation was also found between the expression of collagen type I and diameter of ulcer (Pearson correlation = 0.599, p = 0.05), however, no correlation found between weight loss with the expression of collagen type I (Pearson correlation = -0.102, p = 0.66), and the ulcer diameter (Pearson correlation = 0.022, p = 0.92). Conclusion: Gold sea cucumber had a potential benefit to be used as a traumatic ulcer healing medicament. Water extract of gold sea cucumber able to accelerate traumatic ulcer healing by enhancing the production of collagen type I and reduce the diameter of ulcer. There is a strong correlation between collagen type 1 expression and diameter of ulcer, and a weak correlation found between body weight loss and collagen type I expression, also with reducing ulcer diameter.Keywords: Gold sea cucumber, Stichopus hermanii, healing process, traumatic ulcer.